2020
DOI: 10.35944/jofrp.2020.9.1.010
|View full text |Cite
|
Sign up to set email alerts
|

Social Finance and Sustainable Development Goals: A Literature Synthesis, Current Approaches and Research Agenda

Abstract: The debate, especially in policy circles, around the emergence of Social and Sustainable Finance (SSF), depict as ‘paradoxical’ the contrast between SSF as a relatively under-developed field of knowledge and thought, and yet as an area of practice with ‘vast potential’ that is experiencing an ‘explosion’ in practitioner numbers. Such potential, in term of economic and social value that SSF can deliver, is reflected in the increasing of interest within the public policy-making arena in the achievement of Sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…SIBs are “financial innovation that enables the mobilization of private financing for public sector programs” (Rizzello & Carè, 2016, p. 145). Precisely, SIBs are the financial innovation that contributes to the significant betterment of society (Schinckus, 2017).…”
Section: Cluster Analysismentioning
confidence: 99%
“…SIBs are “financial innovation that enables the mobilization of private financing for public sector programs” (Rizzello & Carè, 2016, p. 145). Precisely, SIBs are the financial innovation that contributes to the significant betterment of society (Schinckus, 2017).…”
Section: Cluster Analysismentioning
confidence: 99%
“…This study identified five clusters, namely (1) people's well‐being, combined with technological innovation, (2) governance, (3) ethical investment and sustainable development, (4) corporate social responsibility (CSR), and (5) transparency, which allow to have practical and theoretical understandings on social finance. Rizzello and Kabli (2020) examined the relationship between social finance and the SDGs; although this study used Google Scholar, Scopus, and WoS databases, it does not use bibliometrics tools, such as VOSviewer or Bibliometrix.…”
Section: Introductionmentioning
confidence: 99%
“…Green inventions, green technical adaptations, basic research toward a carbon-neutral society and multinational businesses (for example, Tesla) are likely to impact future clean technology investments (Liyanage et al. , 2020; Rizzello and Kabli, 2020). Financial markets and the players who administer and communicate their investment logic are heavily reliant on conventional asset classes such as oil, gas, coal, nuclear and allied groupings (Gao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Green bonds (S&P Green Bond US Dollar and S&P Green Bond Select) have a modest market cap in comparison to the cryptocurrency growth since 2013, but both have influenced investor attention. Green inventions, green technical adaptations, basic research toward a carbon-neutral society and multinational businesses (for example, Tesla) are likely to impact future clean technology investments (Liyanage et al, 2020;Rizzello and Kabli, 2020). Financial markets and the players who administer and communicate their investment logic are heavily reliant on conventional asset classes such as oil, gas, coal, nuclear and allied groupings (Gao et al, 2021;Yousaf et al, 2022), but these emerging asset classes are attempting to diversify the present carbon-intensive investing rationale in favor of a more environmentally friendly and carbon-neutral one.…”
mentioning
confidence: 99%